2009
DOI: 10.1590/s1516-89132009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of juvenile dog snapper Lutjanus jocu (Bloch and Shneider, 1801) (Lutjanidae) in intertidal mangrove creeks in Curuçá estuary (Northern Brazil)

Abstract: The diet and feeding ecology of juvenile dog snapper (Lutjanus jocu) were investigated in 92 specimens collected in four intertidal mangrove creeks of Curuçá estuary, Northern Brazil, between September 2003 and July 2004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
(28 reference statements)
0
15
1
Order By: Relevance
“…Despite the fact that Monteiro et al (2009) andPimentel &Joyeux (2010) suggested temporal changes in the diet composition of snappers in the Brazilian coast, we did not observe seasonal variation for L. analis. We believe that this variation is related with the local changes in prey availability (Randal, 1967).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Despite the fact that Monteiro et al (2009) andPimentel &Joyeux (2010) suggested temporal changes in the diet composition of snappers in the Brazilian coast, we did not observe seasonal variation for L. analis. We believe that this variation is related with the local changes in prey availability (Randal, 1967).…”
Section: Discussioncontrasting
confidence: 92%
“…We believe that this variation is related with the local changes in prey availability (Randal, 1967). In fact, Monteiro et al (2009) andPimentel &Joyeux (2010) worked in mangrove environments, which are often subjected to more acute environmental changes than are reef faunas (Sierra et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The spawning season of L. jocu is winter to spring; maturity is reached from 30.5 cm in females and 26.6 cm in males (Freitas et al, 2011). Other biological aspects of the species have been studied in Brazil, such as age and growth by Rezende & Ferreira (2004) and diet by Monteiro et al, (2009). According to the latter authors, L. jocu feeds on many families of crustaceans, mollusks, and teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…Juveniles of Lutjanus jocu, for example, were reported to depend on seasonal variability of preys [8]. Nonetheless, juveniles of salmons were reported to have their preference diet constant despite the fluctuation in the abundance of preys [9].…”
Section: Introductionmentioning
confidence: 99%